Comparison of body weight among hormonal and non-hormonal users in a Malaysian cohort. Issue 1 (February 2019) - Ibrahim, Hafizah; Tengku Ismail, Tengku Alina; Hashim, Noran
الملخص: أهداف البحث: لا تزال زيادة الوزن قضية، لمستخدمات وسائل منع الحمل بسبب زيادة الوزن وانتشار معدل السمنة. تهدف هذه الدراسة المرجعية لمقارنة زيادة الوزن بين موانع الحمل الهرمونية وغير الهرمونية في عيادات الصحة الحكومية في مدينة بهارو، كلنتان، ماليزيا. طرق البحث: تم مشاركة ما مجموعه ٣٨٠ سيدة من اللواتي استخدمن نفس وسيلة منع الحمل لمدة ١٢ شهرا في هذه الدراسة. تم عمل تحليل التباين لمقارنة زيادة الوزن بين مستخدمات موانع الحمل الهرمونية وغير الهرمونية، أثناء دراسة نفس العوامل (العمر، ودخل الأسرة، وعدد مرات الحمل ومؤشر كتلة الجسم الأساسي). النتائج: كانت الطرق الهرمونية هي الأكثر شيوعا. متوسط زيادة الوزن بين مستخدمات الهرمون (المتوسط المعدل ٢.٨، فاصل الثقة ٩٥٪ ٢.٤٥، ٣.٢٤) أعلى بكثير من مستخدمات الطرق غير الهرمونية (المتوسط المعدل ٠.٤٦، فاصل الثقة ٠.٧٣-، ١.٦٥) بعد التحكم في العمر، ودخل الأسرة، وعدد مرات الحمل ومؤشر كتلة الجسم الأساسي. الاستنتاجات: ينبغي التحقق من إمكانية زيادة الوزن بعد استخدام الطرق الهرمونية وينبغي النظر في خيارات أخرى من الطرق غير الهرمونية للحد من زيادة الوزن. Abstract: Objectives: Weight gain remains an issue for contraceptive users due to the high prevalence of obesity. This retrospective study compares the weight gain between hormonal and non-hormonal contraceptive users in government health clinics in Kota Bharu, Kelantan, Malaysia. Methods: A total of 380 women who had used the same contraceptive method for at least twelve months were recruited in this study. Covariance analysis was done to compare the weight gain between hormonal and non-hormonal contraceptive users, while studying the same confounders [age, household income, number of pregnancies, and baseline body mass index (BMI)]. Results: Hormonal methods were more commonly used. The mean weight gain among hormonal users (adjusted mean 2.85, 95% CI 2.45, 3.24) was significantly higher than non-hormonal users (adjusted mean 0.46, 95% CI -0.73, 1.65; p -value <0.001), after controlling for age, household income, number of pregnancies, and baseline BMI. Conclusion: The possibility of weight gain following the use of hormonal methods should be investigated and non-hormonal methods should be considered to prevent weight gain.